Trends of human influenza infection in Chhattisgarh: a retrospective observational study - Sharma, Raj; Bharti, Rupendra K.; Sharma, Sanat; Jaiswal, Mahendra K. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Human influenza virus was recognized as a pandemic in 2009 by the World Health Organization (WHO). Since then many newer incidences was recognized in India, but there was no sufficient data from all state of India. This study will provide data from the Chhattisgarh state of India. Methods: It was a retrospective observational study from December 2015 to November 2017. All patient samples with suspected influenza infection were collected and analysed by Real-time reverse polymerase chain reaction (RT-PCR). Results: 341 patients’ sample was collected and analysed; among these samples, 07.9% of patients have all three serotype of influenza positive. Raipur district has the highest incidence of influenza A followed by Durg and Raigarh district of Chhattisgarh. There was no significant difference between male and female who was affected by the influenza virus. Conclusions: The incidence of Human influenza virus is lesser in Chhattisgarh as compare to the average states of India and the state capital has a higher rate of sample collection as well as positive influenza infection.